A new taxon of Euphorbia (Euphorbiaceae) from the southern Iberian Peninsula (Andalusia, Spain) - Casimiro-Soriguer Solanas, Federico; Hidalgo-Triana, Noelia (Phytotaxa, 2023)
A new species, Euphorbia guadalhorcensis of Euphorbia subgenus Esula, section Paralias is described and illustrated. The new species can be separated from the other species in the section by several morphological characteristics, such as chamaephytic and erect habit, and the presence of indumentum on the leaves, stems, dichasia, cyathia, and fruits. In addition, a morphometric study of the ibero-balearic species of sect. Paralias showed that the seeds of the new species are different by having the longest caruncles and highest relation caruncle length/seed length. The new taxon occurs on the low, xeric, and rocky mountains of Sierra del Hacho de Pizarra and Sierra del Hacho de Álora, both localised in the Guadalhorce River Valley in the province of Malaga (Andalusia, Spain).